THE IMPACT OF INTERACTIVE AND INNOVATIVE METHODS ON STUDENTS’ ARTISTIC COMPETENCE IN VISUAL ARTS EDUCATION - Boboniyozova Roziya Mirsalim qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article investigates the influence of interactive and innovative teaching methods on the development of students’ artistic competence in visual arts education. Emphasis is placed on strategies such as project-based learning, flipped classroom, and digital technologies, which foster creativity, critical thinking, and independent problem-solving skills. Drawing on the research of Shovdirov S.A. and other scholars, the article demonstrates how the integration of modern pedagogical approaches enhances students’ aesthetic perception, artistic literacy, and overall engagement in art education.